2006
DOI: 10.1124/mol.106.025569
|View full text |Cite
|
Sign up to set email alerts
|

Plitidepsin Cellular Binding and Rac1/JNK Pathway Activation Depend on Membrane Cholesterol Content

Abstract: Plitidepsin (aplidin) is a marine cyclic depsipeptide in phase II clinical development against several neoplasias. Plitidepsin is a potent inducer of apoptosis through the sustained activation of Jun N-terminal kinase (JNK). We have reported that this activation depends on the early induction of oxidative stress, activation of Rac1 small GTPase, and the later down-regulation of MKP-1 phosphatase. Using Scatchard and saturation binding analyses, we have found that 14 C-labeled plitidepsin binds to a moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…3C). These results parallel those recently reported for breast, renal, and cervical carcinoma cells (Gonzá lezSantiago et al, 2006;Suá rez et al, 2006). In addition, pretreatment with NSC23766, a specific Rac1 inhibitor, prevented the cytostatic/cytotoxic effect of plitidepsin in a concentration-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…3C). These results parallel those recently reported for breast, renal, and cervical carcinoma cells (Gonzá lezSantiago et al, 2006;Suá rez et al, 2006). In addition, pretreatment with NSC23766, a specific Rac1 inhibitor, prevented the cytostatic/cytotoxic effect of plitidepsin in a concentration-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Our results demonstrate that in melanoma cells plitidepsin causes a rapid activation of Rac1 linked to a strong activation of JNK and p38 MAPK, as has been noted in breast, renal, and cervical carcinoma cells, which leads to a rapid induction of apoptosis (Cuadrado et al, 2004;Gonzá lezSantiago et al, 2006;Suá rez et al, 2006). However, in contrast to these other tumor types, in which plitidepsin does not modulate the cell cycle, at low concentrations it causes G 1 arrest and G 2 /M blockage in SK-MEL-28 and UACC-257 melanoma cells.…”
Section: Dual Effect Of Plitidepsin In Human Melanoma Cells Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, acute activation of JNK through rapid expression of constitutive mutant Rac1 V12 led to apoptosis in thyroid cells (10). Plitidepsin, a potent inducer of apoptosis, was dependent on the Rac1/JNK pathway to function (11). All of these results strongly suggest that the Rac1/JNK cascade is important in DNA damage response-induced cell apoptosis.…”
supporting
confidence: 49%
“…In the subsequent studies, the mitochondrial changes were shown to be caused by different interactions. The sustained activation and phosporylation of c-Jun N-terminal kinase (JNK) by reactive oxygen species (ROS) is recognised as one of the crucial mechanisms in the effects of Aplidin on breast cancer cells (Garcia-Fernandez et al, 2002;Cuadrado et al, 2004;GonzalezSantiago et al, 2006;Suarez et al, 2006). This ROS induction was found to be caused by an alteration in the glutathione homeostasis and by a rapid activation of the small GTP-binding protein Rac (Cuadrado et al, 2003;Gonzalez-Santiago et al, 2006).…”
Section: Discussionmentioning
confidence: 99%